Future of the Ocean: Impact of Human Activities on Marine Systems : G7 Science Academies' Statement 2015 - Deutsche Akademie Der Naturforscher Leopoldina (MyCoRe Community, 2015)
This statement was prepared by the National Academies of Sciences of the G7 states under the leadership of the German National Academy of Sciences Leopoldina to provide scientific advice to the G7 Summit of Heads of State and Governments in Germany in 2015. Human activities are driving major changes in the oceans of the world. One key driver of changes is elevated carbon dioxide (CO2) concentration in the atmosphere caused by human activities. This leads to ocean acidification, warming and deoxygenation, changes in ocean circulation, continued sea level rise, and an altered marine productivity and biodiversity. Other key drivers are pollution with nutrients, chemicals and plastic, overfishing and spreading of invasive species. All of the changes in the ocean have profound effects on human wellbeing and human societies in many regions of the Earth. The G7 Academies of Sciences call for: changing the course of nations’ CO2 emissions, reducing and further regulating man-made pollution of the sea, ending overfishing and preserving marine biodiversity and ecosystem function through research-based management and enhancing international scientific cooperation to better predict, manage and mitigate future changes in the ocean, and their impacts on human societies and the environment. : Diese Stellungnahme wurde von den Nationalen Akademien der Wissenschaften der G7-Staaten unter Federführung der Nationalen Akademie der Wissenschaften Leopoldina zur Beratung des Gipfeltreffens der Staats- und Regierungschefinnen und -chefs der G7- Staaten in Deutschland im Jahr 2015 erarbeitet. Menschliche Aktivitäten verändern die Ozeane dieser Erde grundlegend. Ein wesentlicher Treiber des Wandels ist die erhöhte Konzentration von anthropogenem Kohlenstoffdioxid (CO2) in der Atmosphäre. Diese führt zur Versauerung, Erwärmung und Sauerstoffverarmung der Meere, Veränderungen in der Ozeanzirkulation, einem anhaltenden Anstieg des Meeresspiegels sowie einer veränderten marinen Produktivität und biologischen Vielfalt. Weitere entscheidende Treiber sind Verschmutzung durch Nährstoffe, Chemikalien und Plastik, Überfischung und die Ausbreitung invasiver Arten. Alle Veränderungen in den Meeren wirken sich schwerwiegend auf Gesellschaften und das menschliche Wohlergehen in vielen Regionen weltweit aus. Die Wissenschaftsakademien der G7-Staaten fordern: Änderungen des Kurses der nationalen CO2-Emissionen, die Reduktion und weitere Regulierung anthropogener Meeresverschmutzung, ein Ende der Überfischung sowie den Schutz der Biodiversität und der Ökosysteme der Meere durch forschungsbasierte verantwortliche Bewirtschaftung und die Verbesserung der internationalen Wissenschaftskooperation, um zukünftige Veränderungen der Ozeane sowie deren Auswirkungen auf die menschliche Gesellschaft und die Umwelt besser vorhersagen, handhaben und mildern zu können. : G7 and G20 Statements of the National Academies of Sciences